Exploring the experience of inpatients with severe alcohol use disorder on a managed alcohol program (MAP) at St. Paul's Hospital - Beena P. Parappilly; Emma Garrod; Ryan Longoz; Eric Eligh; Holly van Heukelom; Christopher Kit Fairgrieve; Bernadette Pauly (BMC, 2020)
Abstract Background Managed alcohol programs are a harm reduction approach for people with severe alcohol use disorder that provide alcohol in a structured setting. We examined the patient experience of receiving alcohol after the implementation of a hospital-based managed alcohol program. Methods Using an interpretative descriptive methodology, we conducted interviews with five patients. The criteria for enrollment included continuation of community managed alcohol program or provision of alcohol for stabilization in hospital and ability to provide consent. Results Five themes emerged in the analysis: (1) Reasons for alcohol use highlighting factors leading to alcohol consumption; (2) I'm very appreciative indicating participant's perception of hospital-based managed alcohol program; (3) From just vibrating to calm and It's kinda like a pacifier for me recognizing the impact of hospital-based managed alcohol program on managing withdrawal and on psychological health; (4) I have no need to go anywhere at all demonstrating engagement in healthcare; and (5) Might be nice to have a selection for other people indicating the need for a broader selection of alcohol. Conclusions This study helped to explore the effectiveness of a hospital-based managed alcohol program as experienced by the patients. Overall, participants had a positive experience on hospital-based managed alcohol program. Their perceptions can be used to inform implementation of managed alcohol programs in other hospital settings.